The desorption and reaction of 1-alkenes and 1-alkynes on Cu(111) and copper foils - Miller, Brendan P. (2013)
The adsorption of a series of 1-alkene and 1-alkynes is examined both on Cu(111) single crystals and a polycrystalline copper foil in order to explore the influence of low-coordination sites expected to be present on the copper foil on the chemistry of 1-alkenes. The 1-alkene desorption temperatures increase linearly with the number of carbon atoms in the 1 alkene due to van der Waals´ interaction between the n-alkyl chain and the surface. However, 1-alkenes desorb at temperatures from 60 to 100 K higher on the polycrystalline copper foil than the Cu(111) single crystal due to the presence of low-coordination sites on the foil. In contrast, 1-alkynes up to 1-octyne desorb at ~345 K from both the polycrystalline foil and Cu(111), while 1-nonyne and 1-decyne desorb between 400 and 430 K. This is ascribed to the strong rehybridization of 1-alkynes on copper surfaces that causes the n-alkyl group to move away from the surface, except for 1-nonyne and 1-decyne, where the termini of the alkyl chains are proposed to be able to access the surface. The stabilization of 1 alkenes on the polycrystalline foil allows them to dehydrogenate to form the corresponding 1-alkyne. This effect is ascribed to the presence of low-coordination sites on the polycrystalline sample that stabilize the 1-alkene allowing surface reactions to occur.